Kufal Symbiosis: Collaboration of Artificial Intelligence and Terrorist Organizations - Guna, Wahyu Jati Arya (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This paper delves into the phenomenon of